Trajectories of clinical and parenting outcomes following admission to an inpatient mother-baby unit - Nicole Reilly; Elloise Brake; Nancy Briggs; Marie-Paule Austin (BMC Psychiatry, 2019)
Abstract Background This study aimed to examine trajectories of clinical and parenting outcomes following admission to a mother-baby unit (MBU), and to explore factors associated with these trajectories. Methods Women admitted to an MBU completed the Edinburgh Postnatal Depression Scale (EPDS), Depression, Anxiety and Stress Scale (DASS-21), Karitane Parenting Confidence Scale (KPCS) and Maternal Postnatal Attachment Scale (MPAS) at admission, discharge and 3 months following discharge. Questions assessing psychosocial risk and adult attachment style were also completed at admission, and information relating to service engagement in the time since discharge was collected at follow-up. Additional clinical and demographic information was extracted from the patient medical record. Results Seventy-five women participated in the study. Overall, significant improvements in mean scores on measures of anxiety and parenting confidence were maintained 3-months following discharge. However, the majority of women (93.3%) followed trajectories that were characterised by deterioration in self-reported mother-infant attachment following discharge. 62.9 and 34.6% of women followed trajectories of increased symptoms of depression and stress between discharge and follow-up, respectively. Across measures, the least optimal trajectories, or least optimal scores, at follow-up were associated with less secure maternal attachment style (associated with more anxiety symptoms, poorer parenting confidence and maternal-infant attachment), older maternal age (more depressive symptoms) and increased psychosocial risk (more anxiety symptoms). Conclusions The findings of this study highlight the clinical implications of anxious attachment style for the mental health and parenting outcomes of women admitted to an MBU and the importance of incorporating mother-infant therapy as part of an ongoing management plan. Comprehensive discharge planning and transitional care to help ensure women discharged from an MBU are best supported in the longer term is recommended.